Pemodelan Gerakan Chess Knight dalam Masalah System Produksi - Usman, Ari; Lestari, Yuyun Dwi (Universitas Harapan Medan, 2024)
Artificial Intelligence is a part of computer science that studies how to make computers able to do work like humans do. The horse checker on a chess board has a movement that resembles the letter L. This chess checker is one of the pieces that is very difficult to move and is often the most dangerous checker if you don't pay close attention to each movement. The simulation of this problem provides an n x n chessboard. The goal of this problem is to move a horse from a certain position on the chess board to the desired goal position by simulating all the shortest possible movement solutions to get to that goal position. This problem is also one of the classic problems in artificial intelligence (AI). Solving this problem can use the help of production systems and tracking trees